Increasing the displaced fluid volume of curved metal membranes for diaphragm compressors - Solovev Mikhail; Leonhardt André; Kunke Andreas; Clausmeyer Till (MATEC Web of Conferences)
This study presents the development of an elastically deflectable, bistable diaphragm geometry that enables a significant increase in the displaced volume of diaphragm compressors compared to conventional flat diaphragms. The core concept is to pre-form metal diaphragms in order to maximize the volume of gas displaced per compression cycle. The key challenge in designing such pre-formed membranes lies in identifying a geometry that achieves the highest displaced volume while remaining manufacturable through cold forming without fracture and ensuring purely elastic deflection behavior. Stainless spring steel foil was used as the membrane material. Only dome-shaped geometries were analyzed using finite element (FE) simulations in ABAQUS, excluding forming history. Subsequently, forming simulations including stretch forming and hydroforming were conducted, accounting for springback effects. Selected geometries were experimentally formed and validated using an optical 3D measurement system, and their performance was compared with numerical predictions. The hydroformed diaphragm exhibited the highest fatigue life and enabled a 100% increase in displaced volume compared to the flat membrane